2015
DOI: 10.1111/scs.12223
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative self‐efficacy education vs. usual care for patients undergoing joint replacement surgery: a pilot randomised controlled trial

Abstract: (2016). Pre-operative self-efficacy education vs. usual care for patients undergoing joint replacement surgery: a pilot randomised controlled trial. Scandinavian Journal of Caring Sciences, 30(1), pp. 74-82. doi: 10.1111/scs.12223 This is the accepted version of the paper.This version of the publication may differ from the final published version. Keywords: pre-operative self-efficacy; pain management; hip/ knee replacement. Permanent Authors Contributions:MC, RW, LMA, AF, SP all contributed to study concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 30 publications
(34 reference statements)
0
38
1
1
Order By: Relevance
“…Fragmentation of continuity of care may result in confusing treatment orientations for the patient, with a strong probability of errors and duplications, inadequate follow-up, as well as a lack of preparation/information for the user and informal care providers (3,5,7) . Some authors consider that the existence of structured programs with a focus on preoperative preparation through information, education, walk training and daily life activities training directed at both the patient and the caregiver, has a positive impact when returning home, since they are associated with an improvement in functional capacity at discharge and after discharge (2,13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragmentation of continuity of care may result in confusing treatment orientations for the patient, with a strong probability of errors and duplications, inadequate follow-up, as well as a lack of preparation/information for the user and informal care providers (3,5,7) . Some authors consider that the existence of structured programs with a focus on preoperative preparation through information, education, walk training and daily life activities training directed at both the patient and the caregiver, has a positive impact when returning home, since they are associated with an improvement in functional capacity at discharge and after discharge (2,13) .…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative preparation and the organization of care according to the postoperative rehabilitation promote positive and sustainable results, not only in the short term but also in the long term (2,13) .…”
Section: Discussionmentioning
confidence: 99%
“…A moderate, statistically significant effect was demonstrated in favour of the psychological intervention ( g = −0.26 (−0.49, −0.03), P = 0.024), with non‐significant low heterogeneity ( I 2 = 29.46, P = 0.21). Of the six studies, four utilized relaxation techniques, one examined CBI and one utilized mixed therapies. There was no evidence of publication bias based on Egger's regression analysis ( P = 0.60; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Findings were similarly polarized looking at pain outcomes in the subacute time period, with three studies 27,31,34 reporting statistically significant reductions in pain with the use of psychological interventions, but two studies 35,42 finding no difference. Only one study 31 reported pain outcomes at longer term follow-up, finding statistically significant improvement with the use of guided imagery.…”
Section: Painmentioning
confidence: 99%
See 1 more Smart Citation